The logic of competitive influence-seeking: Russia, Ukraine, and the conflict in Donbas - Маляренко, Тетяна Анатоліївна; Маляренко, Т. А.; Маляренко, Татьяна Анатольевна; Maliarenko, Tetiana A.; Malyarenko, Tatyana; Wolff, Stefan (informa UK Limited, trading as taylor & francis Group, 2018)
The crisis in Ukraine since late 2013 has seen four successive internationally mediated agreements that have been at best partially implemented. Drawing on extensive fieldwork and 42 key informant interviews sides, we explain this outcome with reference to the logic of competitive influence-seeking: Russia is currently unable to achieve a friendly and stable regime in Kyiv and thus hedges against the consolidation of an unfriendly pro-Western and stable regime by maintaining its control over parts of eastern Ukraine and solidifying the dependence of local regimes there on Russian support. This gives Russia the opportunity to maintain the current status quo or settle for re-integration terms through which Russia can sustain long-term influence over Ukraine’s domestic and foreign policy. We conclude by reflecting on the consequences of competitive influence-seeking in the post-Soviet space: the likely persistence of low-intensity conflict in Ukraine; the further consolidation of territorial divisions in other post-Soviet conflicts; and the need for policy-makers in Russia and the West to prioritize the management of the consequent instability.

Криза в Україні з кінця 2013 року призвела до чотирьох послідовних угод, що здійснюються за посередництвом міжнародних органів, які в кращому випадку виконувались частково. Спираючись на велику роботу на місцях та на 42 ключових інтерв’ю зі сторонами, ми пояснюємо цей результат, посилаючись на логіку конкурентного пошуку впливу: Росія в даний час не може досягти доброзичливого та стабільного режиму в Києві і, таким чином, захищається від консолідації недружніми прибічниками Західного та стабільного режиму, підтримуючи контроль над частинами Сходу України та підсилюючи залежність місцевих режимів там від російської підтримки. Це надає Росії можливість зберегти нинішній статус-кво або погодитися на умови реінтеграції, завдяки яким Росія може тривалий час підтримувати вплив на внутрішню та зовнішню політику України. На закінчення ми розмірковуємо про наслідки конкурентного пошуку впливу на пострадянському просторі: ймовірність збереження конфлікту низької інтенсивності в Україні; подальше закріплення територіального поділу в інших пострадянських конфліктах; і необхідність того, щоб політики у Росії та на Заході надавали першочергову увагу управлінню послідуючою нестабільністю

Кризис в Украине с конца 2013 года привел к четырем последовательным соглашениям при международном посредничестве, которые в лучшем случае были выполнены частично. Опираясь на обширные полевые исследования и собеседования с 42 ключевыми информантами, мы объясняем этот результат со ссылкой на логику конкурентного стремления к влиянию: Россия в настоящее время не может добиться дружественного и стабильного режима в Киеве и, таким образом, ограждает себя от консолидации недружественных сторонников Западного и стабильного режима за счет сохранения контроля над частями восточной Украины и усиления зависимости местных режимов от поддержки России. Это дает России возможность сохранить текущий статус-кво или согласиться на условия реинтеграции, с помощью которых Россия сможет поддерживать долгосрочное влияние на внутреннюю и внешнюю политику Украины. В заключение мы размышляем о последствиях конкурентного стремления к влиянию на постсоветском пространстве: вероятное сохранение конфликта низкой интенсивности на Украине; дальнейшее усиление территориального разделения в других постсоветских конфликтах; и необходимость того, чтобы политики в России и на Западе уделяли первоочередное внимание управлению последующей нестабильностью.
Malyarenko T. The logic of competitive influence-seeking: Russia, Ukraine, and the conflict in Donbas / T. Malyarenko, S. Wolff // Post-Soviet Affairs. - Vol. 34, issue 4. - 2018. - pp. 191–212. – Режим доступу: https://www.tandfonline.com/doi/full/10.1080/1060586X.2018.1425083
Keywords: етнічний конфлікт; громадянська війна; відмова держави; тендітність держави; управління міжнародними конфліктами; врегулювання конфлікту; ethnic conflict; civil war; state failure; state fragility; international conflict management; conflict settlement; этнический конфликт; гражданская война; отказ государства; хрупкость государства; управление международными конфликтами; урегулирование конфликта; Research Subject Categories::SOCIAL SCIENCES